PENATAAN PERMUKIMAN NELAYAN KELURAHAN TANJUNG KERAMAT KOTA GORONTALO - Nasir, Yosan; Arifin, Sri Sutarni; Tatura, Lydia S. (JAMBURA Journal of Architecture, 2022)
ABSTRAK.  Kelurahan Tanjung Kramat merupakan salah satu permukiman penduduk di Kota Gorontalo yang sebagian besar masyarakat berpropesi sebagai nelayan. Banyak sarana dan prasarana dalam kawasan permukiman yang masih belum sesuai dengan standar permukiman yang telah diatur pemerintah dan banyak masalah kependudukan yang terjadi di kawasan permukiman antara lain, pengolahan sampah, kebutuhan ruang dan fasilitas untuk masyarakat nelayan yang masih kurang. Tujuan penataan permukiman ini untuk mendapatkan gambaran kawasan permukiman yang layak sesusai standar permukiman yang berlaku dengan sarana dan prasarana yang memadai.Kata Kunci: Penataan Permukiman Nelayan, Tanjung Kramat, Arsitektur Tropis.ABSTRACT. Tanjung Kramat Subdistrict is one of the residential areas in Gorontalo City where most of the people work as fisherman. Many facilities and infrastructure in residential areas are still bellow the standards set the government. Many population problems that occur in residential areas, including waste management, space requirements, and facilities for fishing communities are still lacking. The purpose of this settlement standards with adequate facilities and infrastructure. The results of the design were able to organize settlements with all activities and infrastructure that support the fishing community of Tanjung Kramat Subdistrict. The results of the the report were in the form of design concepts and applications to design objects as a guide for continuing the arrangement of fisherman’s settlements in Tanjung Kramat Subdistrict, Gorontalo City. Keywords: fishermen Settlement Arrangement, Tanjung Kramat, Tropical Architecture.